Deliberative Agonism and Agonistic Deliberation in Hannah Arendt. Issue 161 (1st December 2019) - Ballacci, Giuseppe
Abstract : In the literature there are two well-established but opposite readings of Arendt: as an agonistic theorist and as a deliberative one. In between these two positions a smaller number of scholars have argued that in Arendt these two dimensions can to a large extent be reconciled. This paper follows this third path but tries to bring it one step further. In particular, it defends the idea that those scholars who have proposed this third reading of Arendt have fallen short of revealing the degree to which deliberation and agonism are, for her, interwoven. Through an original reading of Arendt's views on judgment, persuasion, distinction and Eichmann's banality, the paper clarifies why, for her, agonism and deliberation are not only compatible but actually mutually dependent. In other words, it clarifies why she believes that there can be no deliberation without agonism and no agonism without deliberation.